The development of the Cystectomy‐Pathway Assessment Tool (C‐PAT): a concise tool to assess the quality of care in the cystectomy pathway. (27th July 2021) - Uren, Alan D.; Cotterill, Nikki; Abrams, Paul; Catto, James W. F.; Patel, Biral; McGrath, John; Ahmed, Iram; Rowe, Edward
Abstract : Objectives: To develop and test the psychometric properties of a concise, patient‐reported questionnaire, designed to assess key aspects of the radical cystectomy (RC) patient pathway that are important to both patients and clinicians. Patients and Methods: Draft items were developed by a consultation with a 13‐member expert clinical panel, and the in‐depth qualitative analysis of 14 semi‐structured interviews with patients who had received RC within the previous 18 months. A further nine cognitive interviews with patients refined the items and ensured they were easy to complete. Pilot testing in 122 patients recruited from five hospitals in England tested the properties of validity and reliability of the resulting 17‐item questionnaire. Results: Patients and clinicians identified the following aspects as important for the delivery of quality patient care. These included timely referral and initial test results; an explanation of risk/benefits of treatment; access to a cancer nurse specialist; training and support in stoma management; timely surgery, surgical complications, and timely follow‐up. Pilot testing showed missing data was low (≤3% for all items), and between 73% and 89% of the responses to items were the most positive about their care (indicating ceiling effects). Five items were identified using factor analysis as being statistically related (Cronbach's α 0.76, intraclass correlation coefficient test–retest reliability of 0.95) and formed the scored part of the tool 'care and support', scored 0–16. There was insufficient evidence at this stage to show the tool was capable of measuring differences between cancer centres. Conclusion: We have developed a questionnaire that captures aspects of quality of care within the RC patient pathway. The results support the validity and reliability of the 17‐item Cystectomy‐Pathway Assessment Tool (C‐PAT). We envisage the tool can be the basis for audit of the patient reported assessment of the quality of care for individual cancer centres.